Long-term district-scale geothermal exchange borefield monitoring with fiber optic distributed temperature sensing. (March 2018) - McDaniel, Adam; Fratta, Dante; Tinjum, James M.; Hart, David J.
Highlights: Fiber optics distributed temperature sensing (DTS) allows high resolution monitoring of district scale geothermal borefields. Observed variation of heat flow in the borefield is linked to saturation and lithology. Advection and convection both play a significant role in heat transport in this geothermal borefield. District scale geothermal exchange fields are often subject to overheating due to imbalanced heating and cooling loads. Abstract: Fiber optic (FO) distributed temperature sensing (DTS) was used for long-term monitoring of a 280-m by 360-m geothermal exchange borefield with 2596 boreholes to quantify the role of groundwater flow and thermophysical properties on subsurface heat transfer and storage. Most district-scale borefields are subject to a sustained imbalance in heating or cooling loads and experience yearly subsurface temperature increases that may, without corrective action, lead to diminished borefield performance and unsustainable operation. This research provides a template to advance techniques to optimize district-scale borefield performance using calibrated, long-term FO-DTS monitoring of field temperatures.